PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN : STUDI KASUS: BNI KCP UNIVERSITAS BRAWIJAYA MALANG - Sang Arya Wiratama; Fullchis Nurtjahyani (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
In improving and enhancing services to consumers, business organizations must continue to innovate in maintaining the satisfaction of existing customers. The best way to build relationships with customers can be realized by building customer relationship management. In general, the aim of this research is to find out whether customer relationship management and service quality simultaneously influence customer purchasing decisions at BNI KCP Universitas Brawijaya Malang. The approach in this research is a quantitative approach using multiple linear regression analysis methods. Based on the research results, it is known that customer relationship management partially has a positive and significant effect on purchasing decisions, and service quality also partially has a significant effect on purchasing decisions at BNI KCP Universitas Brawijaya Malang. Furthermore, if tests are carried out on these two variables, it is known that customer relationship management and service quality together have a positive and significant effect on purchasing decisions at BNI KCP Universitas Brawijaya Malang.